If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 1) = x Reorder the terms: 3(1 + 4x) = x (1 * 3 + 4x * 3) = x (3 + 12x) = x Solving 3 + 12x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + 12x + -1x = x + -1x Combine like terms: 12x + -1x = 11x 3 + 11x = x + -1x Combine like terms: x + -1x = 0 3 + 11x = 0 Add '-3' to each side of the equation. 3 + -3 + 11x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 11x = 0 + -3 11x = 0 + -3 Combine like terms: 0 + -3 = -3 11x = -3 Divide each side by '11'. x = -0.2727272727 Simplifying x = -0.2727272727
| -2-3k=1 | | -15(-18x+21)=9(-3x+229) | | -40=-24t | | 5(a-2)+15=45 | | -15(-18x+21)=(-3x+229) | | 64x+30y=180 | | 24*8= | | i^8= | | h=20-16t^2+32t | | Y=2x^2+8x | | 5/4a+1/2=7/9 | | -6+3n=-7(n+8) | | 5x-4=12-2x | | 10d=200 | | X+0.6y=88 | | 6n-28=-30+4n | | -6+3n=-7 | | 4x+2=6+4x | | 10+d=200 | | -27=6y | | 6y+5=2y+7 | | 25n^2-20n=1 | | 10x-4=11+9x | | -6=z/4 | | x-0.7=8.86 | | 4x-(9-3x)=8x-men | | -13+x=54 | | (X+3)(X+9)=0 | | 2a/3-4-3=-2/3 | | -19p=-57 | | -(k+5)=-6k | | -222=-6x-6(x+25) |